2008
DOI: 10.1264/jsme2.me08541
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification Activity and Relevant Bacteria Revealed by Nitrite Reductase Gene Fragments in Soil of Temperate Mixed Forest

Abstract: Denitrification activity and bacterial community constituents were investigated in both well-drained and poorly drained soils of a temperate forest in central Japan by 15 N tracer experiments and a cloning-sequencing approach. Denitrification activity was much higher in wet soil than in dry soil, based on 15 N 15 N ( 30 N 2 ) and 15 N 15 NO ( 46 N 2 O) production. Labeled nitrate ( 15 NO 3 − ) was immediately reduced to 30 N 2 in wet soil, whereas it was only reduced to 46 N 2 O in dry soil. Thus, the wet soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 39 publications
1
21
1
Order By: Relevance
“…Prokaryotic denitrification, fungal denitrification, ammonium oxidation, and nitrate ammonification have been nominated as soil microbial sources of N 2 O (1, 14, 26, 38, 49, 50, 57). Community analysis specific to degrading nodules that emit N 2 O found many microorganisms that potentially produce N 2 O (20), including denitrifying bacteria such as Acidovorax (19) and Enterobacter (2); Bradyrhizobium (25), Salmonella (48), Xanthomonas (52), and Pseudomonas (36), which have functional genes and/or activities for denitrification; and Fusarium , a denitrifying fungus (45).…”
Section: Discussionmentioning
confidence: 99%
“…Prokaryotic denitrification, fungal denitrification, ammonium oxidation, and nitrate ammonification have been nominated as soil microbial sources of N 2 O (1, 14, 26, 38, 49, 50, 57). Community analysis specific to degrading nodules that emit N 2 O found many microorganisms that potentially produce N 2 O (20), including denitrifying bacteria such as Acidovorax (19) and Enterobacter (2); Bradyrhizobium (25), Salmonella (48), Xanthomonas (52), and Pseudomonas (36), which have functional genes and/or activities for denitrification; and Fusarium , a denitrifying fungus (45).…”
Section: Discussionmentioning
confidence: 99%
“…Hawkes et al (36) showed that changes in the gross nitrification rate along with changes in the plant community after exotic plant invasion in grasslands could be explained by the population size of AOB. The basic concept linking microbial community dynamics with N biogeochemistry apply to the majority of other dissimilating processes in N-cycling, including N-fixation, nitrite oxidation, denitrification, N 2 O reduction, and anammox (5, 38, 43, 58, 67, 100, 135). Spatial variations in N 2 O/N 2 emission potential in a grassland pasture can be described using spatial variations in the relative abundance of nirS and nirK in denitrifiers to nosZ in denitrifiers and non-denitrifies (93).…”
Section: Relationship Between Microbial Community Dynamics and N Biogmentioning
confidence: 99%
“…1a. Katsuyama et al (2008) reported denitrification activities of surface soils collected from the area near SG1 (254-505 nmol N/g dry soil/h) and the groundwater collected from SG1-250 (from 1.4 Â 10 À4 to 1.7 Â 10 À3 nmol N 2 /ml/h). In addition, Koba et al (1997) examined the concentration and d 15 N of NO 3 À in soil solutions collected in the SG1 area and found the occurrence of denitrification with response to the precipitation.…”
Section: Study Sitementioning
confidence: 99%